Investigation on shakedown response-behavior of thawed subgrade soils under long-term traffic loading - Wang, Shujian; Li, Xiangyang; Ti, Yanzheng; Zhang, Xiaoning; Yin, Tao; Wang, Ruibing; Jiang, Xiufeng; Su, Zhikai; Hao, Jianwen (Frontiers in Earth Science, 2024)
The shakedown state of subgrade is crucial for the sustainable design and long-term stability evaluation of pavement structures. In order to characterize the plastic deformation and shakedown behavior of subgrade soil in seasonal frozen regions, the cyclic triaxial tests were conducted on the thawed subgrade soil after seven cycles of freeze-thaw. The influences of numbers of cycle loading, amplitude of cyclic deviator stress and confining stress were considered as variables. The evolution features of accumulative plastic strain, accumulative plastic strain rate and critical dynamic stress were experimentally analyzed. Based on the shakedown theory, the ensuing discoveries were that the accumulative plastic strain response-behavior of thawed subgrade soil was typically divided into plastic shakedown, plastic creep and incremental collapse under the long-term cyclic loading. Furthermore, the shakedown standard for thawed subgrade soil was also proposed based on evolution of accumulative plastic strain rate.The critical dynamic stresses can be obtained by the proposal formula to determine the different plastic deformation range.